1979
DOI: 10.3758/bf03196934
|View full text |Cite
|
Sign up to set email alerts
|

The time course of the verbal prediction effect

Abstract: Choice reaction times following correct verbal predictions of the presented stimulus are faster than after incorrect predictions. Two experiments examined the influence of the time interval (PSI) between the prediction and the stimulus on the magnitude of the prediction effect. Experiment 1 used equiprobable stimuli and showed a smaller prediction effect at a 2-sec PSI than at a 0-or .5-sec PSI. Experiment 2 used unequal-probability stimuli and showed that the prediction effect was independent of PSI when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…A mismatch between verbalized expectation (i.e., the infrequent stimulus) and presented stimulus (i.e., the frequent stimulus) might have comparatively moderate average RT costs, because participants changed their mind on many such trials and (different from what they originally said) expected the frequent stimulus when it actually occurred. In line with this reasoning, Acosta and Hinrichs (1979) observed that the mismatch effect decreases with stimulus waiting time only on trials in which participants had verbalized that they were expecting the infrequent stimulus. The delay had no impact on the mismatch effect in trials in which they verbalized that they expected the frequent stimulus.…”
Section: Motivational Aspects -Commitment To Truthfully Verbalize An supporting
confidence: 50%
See 2 more Smart Citations
“…A mismatch between verbalized expectation (i.e., the infrequent stimulus) and presented stimulus (i.e., the frequent stimulus) might have comparatively moderate average RT costs, because participants changed their mind on many such trials and (different from what they originally said) expected the frequent stimulus when it actually occurred. In line with this reasoning, Acosta and Hinrichs (1979) observed that the mismatch effect decreases with stimulus waiting time only on trials in which participants had verbalized that they were expecting the infrequent stimulus. The delay had no impact on the mismatch effect in trials in which they verbalized that they expected the frequent stimulus.…”
Section: Motivational Aspects -Commitment To Truthfully Verbalize An supporting
confidence: 50%
“…It is conceivable that an expectation truthfully verbalized changes before stimulus onset. For instance, Acosta and Hinrichs (1979) suggested that changes in expectation after verbalization might account for the observation that expectation mismatch effects in RT decrease with longer interval between expectation and stimulus. Specifically, they suggested that in trials in which participants verbalize that they are expecting the infrequent stimulus, this verbalization might correctly capture what participants are expecting at the time they utter the expectation.…”
Section: Motivational Aspects -Commitment To Truthfully Verbalize An mentioning
confidence: 97%
See 1 more Smart Citation
“…It is possible that these results may reflect the operation of guessing biases. It is known that choice RT is shorter when a stimulus guess is confirmed than when it is not confirmed (Acosta & Hinrichs, 1979). Perhaps subjects guessed which stimulus (1 00 or 300) would appear.…”
Section: Discussionmentioning
confidence: 99%
“…That is, one might argue that the subjects did not or could not establish a category set per se, but, instead, attempted to establish a set for each individual stimulus in a category. Perhaps they could not maintain multiple sets simultaneously and, therefore, switched back and forth from one stimulus set to the other during the interval following the category prediction (Acosta & Hinrichs, 1979). Since sometimes the stimulus would agree with their momentary set and sometimes it would not, there would be a benefit but also a cost associated with correct category predictions.…”
Section: Prediction Accuracy 505mentioning
confidence: 99%